Kajian Teologis tentang Gaya Hidup Yesus untuk Memintas Rantai Hedonisme: Menurut Aristippus - Sanderan, Rannu; Sampe, Naomi (Institut Agama Kristen Negeri Toraja, 2023)
This research aims to explore the image the concept of God in the context of human life immersed in the vortex of hedonism. The research will combine the approaches from philosophy and theology to uncover the secrets of the grandeur of God's image and how a deeper understanding of His presence can bring salvation and happiness to human life. The study will examine the values and essence of the lifestyle of Jesus Christ, which can serve as the center of spirituality for Christians, using qualitative research methods and a phenomenological perspective to understand the subjectivity of the human beings involved.The research presents the concepts of wisdom contained within the genuine concept of human beings as the image and likeness of God and how these concepts can be applied in the lives of people faced with temptation and greed.It is hoped that the results of this research will make a significant contribution to our understanding of the spirituality of Jesus Christ and lead us to a more accurate and proper understanding of the essence of life. Furthermore, it is expected that this research will provide inspiration and guidance for readers to achieve righteousness, wisdom, and greatness in their lives by fully referring to the divinity of Jesus.